การออกแบบประกันชีวิตแบบบำนาญ - ณิชาธร ศรีศิลปอุดม (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
In this project, we study annuity life insurance designing and we bring the patterns of "AIA Annuity Smart" @55, @60 and @65 to study and find the internal rate of return when the insurer die in each age. Moreover, we use Microsoft Excel and Excel VBA to calculate internal rate of return, annuity premiums and annuity benefits.